Carbon nanotube introduction, characterisation and application - Anon (Universiti Malaysia Perlis (UniMAP), 2011)
Organized by Institute of Nano Electronic Engineering, Universiti Malaysia Perlis (UniMAP), 25th July 2011 at Seminar Room Tun Za'ba, Unit Kesihatan & Keselamatan Pekerjaan, Seriab Campus, Perlis, Malaysia.